PENGOLAHAN DATA GPS UNTUK KENDARAAN LISTRIK OTONOM - Putra, Nyoman Triyoga Arika; Satyawan, Arief Suryadi; Wulandari, Ike Yuni; Ariffin, Denden Mohamad (Akademi Angkatan Udara, 2022)
Information and communication technology continues to show its development, and one of the technological developments in the information sector is the Global Positioning System (GPS). GPS technology is designed by utilizing satellites in space called the Global Navigation Satellite System (GNSS) whose application can be used in autonomous electric vehicles. Therefore, this study aims to design a GPS data processor on autonomous electric vehicles. The method used is using a Raspberry Pi 4 mini computer and a Neo 6M GPS module and the basic application is using the Python programming language. The application created has an output in the form of a display that shows the data obtained from the satellite and automatically the data will be stored in the form of an Excel file. The data in the Excel file will be compared with data from Google Maps. From the results of the research that has been done, the use of the Neo 6M GPS module in this application has an economical price, and the location data received is quite accurate, the GPS can be used indoors or outdoors, and even in rainy conditions the GPS can still receive signals well. these results can be applied to the autonomous electric vehicles technology.